Trauma in pregnancy clinical practice guidelines: systematic review. (12th December 2022) - De Vito, Marika; Capannolo, Giulia; Alameddine, Sara; Fiorito, Roberto; Lena, Alessandro; Patrizi, Lodovico; D' Antonio, Francesco; Rizzo, Giuseppe
Abstract: Purpose: To objectively evaluate the methodological quality and clinical heterogeneity robustness of the published clinical practice guidelines (CPGs) on the management of trauma in pregnancy. Materials and methods: Pubmed, Google Scholar, UpToDate, and Scopus Database were searched. The risk of bias and quality assessment of the included CPGs were performed using "The Appraisal Of Guidelines for Research and Evaluation (AGREE II)" tool. The following points relating to the management of trauma during pregnancy were addressed: quality of evidence assessment, classification of recommendations, main causes of trauma in pregnancy, importance of correct use of seat belts, ultrasound scans and/or pregnancy test in every female of reproductive age, description of physiological changes in pregnancy, classification in primary and secondary survey, primary survey based on ABCD Approach, fetus viable based on the weeks, radiographic studies for maternal evaluation, duration of fetal monitoring, use of anti-D immunoglobulin in rhesus-D-negative pregnant trauma patients, description of dose of RhD-Ig, the way to define gestational age if it was undetermined, descriptions of obstetrical complications, use of tetanus vaccination, and timing to perimortem cesarean section (CS). Results: Six CPGs were included. Quality of evidence assessment was described in 16.7% of CPGs (1/6), while it was not reported in 83.3% (5/6). Classification of recommendations was reported in 50% (3/3) of the CPGs. Motor vehicle crash was reported as the main cause of trauma in pregnancy in all the CPGs included in the present review, despite that the importance of a correct use of seat belts was described only in the 50% (3/6). Definition of fetal viability was also different among the included CPGs; in 50% (3/6) defined a fetus viable when it from 23 weeks, 33.3% (2/6) from 24 weeks, and 16.7% (1/6) from 20 weeks of gestation. Regarding the type of fetal monitoring, 33.3% (2/6) CPGs recommended CTG assessment at least every 4 h, 16.7% (1/6) at least every 6 h, 33.3% for 24 h if there are not reassuring signs and 16.7% (1/6) did not specify the duration of monitoring. Recommendations about the use of anti-D-immunoglobulin in rhesus-D-negative pregnant were also heterogeneous: 50% (3/6) of the CPGs suggested administration in all rhesus-D-negative pregnant women, 16.7% (1/6) only according to gestational age at trauma or in case of significant abdominal trauma, and 16.7% (1/6) only in case of positive Kleihauer test while 16.7% (1/6) did not specify it. Administration of tetanus vaccination was suggested in in 33.3% (2/6) of CPGs. Finally, there were different descriptions of timing to perimortem CS: 33.3% (2/6) of CPGs claims to do CS no later than 4 min, 50% (3/6) no later than 5 min, and 16.7% (1/6) does not describe timing for CS. The AGREE II standardized domain scores for the first overall assessment (OA1) had a mean of 69%. Only three CPGs scored more than 60% and revealed a consensus agreement between the reviewers on recommending the use of these CPGs. Conclusion: There is clinical heterogeneity in some of the most relevant aspects of the management of pregnant women with trauma. The findings from this systematic review highlight the need for up to date and shared guidelines promoted by the main body societies in order make management of pregnant women with trauma homogenous.